Analisis Bahan Ajar Fisika Berdasarkan Perspektif Education for Sustainable Development - Rina Wijayanti; Fenny Roshayanti; Irna Farikhah; Nur Khoiri; Joko Siswanto (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to describe the results of the analysis of physics teaching materials for high school energy sources based on the perspective of Education for Sustainable Development (ESD). The research method used is descriptive quantitative research. The population in this study were all materials in physics teaching materials for class XII in Pemalang Regency with samples of energy sources in 5 class XII teaching materials used by teachers in Pemalang Regency. The research instrument was in the form of a text / unit check list analysis based on the ESD indicator to obtain data.The results of the study found that the teaching materials used represented the ESD theme with an average appearance proportion of 21.56%, for the socio-cultural aspects of 8.05%, for environmental aspects 7.53% and 5.98% for economic aspects. From the results of research based on requests to develop ESD-based teaching materials on energy sources.